2015
DOI: 10.1111/nbu.12143
|View full text |Cite
|
Sign up to set email alerts
|

New tools for personalised nutrition: The Food4Me project

Abstract: Personalised nutrition can be considered on three levels, with nutritional advice tailored according to an individual's dietary intake, phenotype or genotype. Personalised nutrition has the potential to become an effective strategy for improving dietary behaviours, with numerous studies demonstrating that personalised advice is more effective than generic advice. Although personalised nutrition is in its early stages, recent advances in technology and research innovation have led to an evolution in both the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Advanced tools and innovative approaches in nutrition assessment are being developed within the Food4Me project (food4me.org). This project, which started in 2011, is carried out by an international consortium focused on the translation of current nutrition knowledge into tailored diets and nutritional advices by meeting three fundamental elements: reliable dietary intake assessment, deep phenotyping (metabotyping), and universal genotyping [ 160 ]. The Food4Me project represents a step forward in the potential application of precision nutrition, since in collaboration with stakeholders from different areas (consumers, industry, regulators, etc.)…”
Section: Recent Advances In Precision Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced tools and innovative approaches in nutrition assessment are being developed within the Food4Me project (food4me.org). This project, which started in 2011, is carried out by an international consortium focused on the translation of current nutrition knowledge into tailored diets and nutritional advices by meeting three fundamental elements: reliable dietary intake assessment, deep phenotyping (metabotyping), and universal genotyping [ 160 ]. The Food4Me project represents a step forward in the potential application of precision nutrition, since in collaboration with stakeholders from different areas (consumers, industry, regulators, etc.)…”
Section: Recent Advances In Precision Nutritionmentioning
confidence: 99%
“…It is worth highlighting that the optimal assessment of nutrient intake remains the foundation for personalized nutritional advice in the Food4Me study [ 160 ]. In this regard, dietary data was collected by a validated online FFQ [ 163 , 164 ] and participants received regular feedback with practical advice to improve, increase or decrease, the intake of specific nutrients.…”
Section: Recent Advances In Precision Nutritionmentioning
confidence: 99%
“…The Food4Me study was designed to determine the efficacy of different levels of personalised nutrition: based on diet intake alone; diet and phenotypic biomarkers; and diet, phenotype and genotype. Results showed that personalisation of food-based dietary advice based on an individual's dietary intake was more effective than generic public health advice, although in that study, no further benefit resulted from the addition of phenotypic or genetic advice ( 17 , 18 ) . The Food4Me dietary advice was based on a decision tree executed manually by researchers during the study to create a report that was sent via e-mail.…”
Section: Introductionmentioning
confidence: 79%
“…This has led to the European Union (EU) Food4Me project which aims to provide answers and new technologies to shape our thinking about personalised nutrition and extend the current state-of-the-art by: (1) developing new scientific tools for the exploration of dietary, phenotypic and genotypic data in the delivery of personalized nutrition using an internet approach; (2) assessing the validity of delivering a personalised nutrition service in a Proof of Principal (PoP) research study, involving a large cohort of 1280 volunteers across seven EU states [ 18 ]. Results of the PoP study showed that an internet-based personalised nutrition intervention was effective in improving dietary behaviors compared with conventional population-based advice [ 19 ].…”
Section: Improvement Of Individual Nutritional Needsmentioning
confidence: 99%